2022
DOI: 10.1007/s43441-021-00364-y
|View full text |Cite
|
Sign up to set email alerts
|

Valuation and Returns of Drug Development Companies: Lessons for Bioentrepreneurs and Investors

Abstract: Objectives This study evaluates the association of Biopharma company valuation with the lead drug’s development stage, orphan status, number of indications, and disease area. We also estimated annual returns Bioentrepreneurs and investors can expect from founding and investing in drug development ventures. Methods SDC Thomson Reuter and S&P Capital IQ were screened for majority acquisitions of US and EU Biopharma companies developing new molecular enti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 37 publications
(58 reference statements)
0
16
0
Order By: Relevance
“…Furthermore, scientists leverage new technologies, including next-generation sequencing, high throughput screening, or machine learning, to quickly test hypotheses and identify optimal patient populations (and indications) for a drug [ 31 , 32 ]. Discovering platform technologies, such as targeted therapies or immuno-therapies, which can be used across multiple diseases, are especially desired and valued by investors [ 1 , 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, scientists leverage new technologies, including next-generation sequencing, high throughput screening, or machine learning, to quickly test hypotheses and identify optimal patient populations (and indications) for a drug [ 31 , 32 ]. Discovering platform technologies, such as targeted therapies or immuno-therapies, which can be used across multiple diseases, are especially desired and valued by investors [ 1 , 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, multi-indication drugs offer dynamic efficiency gains for patients and manufacturers as lengthy and costly research and pre-clinical testing efforts only occur once per drug. Expanding drugs to new indications increases revenues, profits, returns, and valuations for manufacturers [ 4 , 5 ]. However, pricing and reimbursement mechanisms have not evolved at the same pace as pharmaceutical development, intensifying concerns about the affordability of new drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst this observation could suggest that a large part of indication development is random, additional variables may be necessary to fully explain companies’ decision making in pharmaceutical development. For instance, variables characterizing an indication’s peak sales and competitive environment, the pharmaceutical company’s portfolio size, R&D partnerships of certain indications, licensing agreements, mergers and acquisitions, and underlying market conditions may influence economic decision of pharmaceutical companies throughout the drug development process [ 10 , 11 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, pharmaceutical companies are incentivized to pursue research and development (R&D) in diseases with a high unmet therapeutic need with expedited clinical development and regulatory approval timelines [ 9 ]. Michaeli et al previously demonstrated this strategy yields high company valuations and excess financial returns for Bioentrepreneurs and Investors [ 10 , 11 ]. Arguably more substantial than R&D incentives could be the monetary incentive created by uniform pricing of multi-indication drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Evidently, Biopharma firm valuation is mainly subject to the lead product's development stage [10,[20][21][22][23]. However, knowledge on factors that explain the valuation dispersion within development stages is scarce.…”
Section: Introductionmentioning
confidence: 99%